The Effect of Streetscape Characteristics on the Distinctiveness of Place Identity in the Kayutangan Corridor According to Visitors' Perceptions - Nur'izzah, Nadhilah; Ernawati, Jenny; Santosa, Herry (RUAS, 2025)
Place identity is an important aspect in the development of historic areas, particularly in strengthening the visual appeal and cultural value of a region. The Kayutangan Corridor is one of the iconic areas in the center of Malang City that has been revitalized into a modern, pedestrian-friendly heritage corridor. This study aims to examine the influence of streetscape characteristics on place identity, with a focus on the dimension of distinctiveness. This study uses a quantitative approach, employing a survey of 160 respondents who are visitors to the Kayutangan corridor. The data was analyzed using multiple linear regression techniques to test the influence of each streetscape element on the perception of distinctiveness. The results showed that three characteristics of streetscape elements had a significant influence on distinctiveness, namely vegetation composition, visual furniture, and aesthetic furniture, with a contribution of 60.9%. These elements not only strengthen the visual character of the area but also create a distinctive image that differentiates the Kayutangan corridor from other corridors. These findings emphasize the importance of contextual streetscape design as part of a strategy for preserving the identity of the area and developing heritage-based tourism.